An investigation of the effects of the vehicle terror suicide attack in the urban area - Savas, Sedat; Bakir, Dursun (Pergamon-Elsevier Science Ltd, 2023)
In this study, the explosion that occurred due to a suicide attack in Elazig Province in Turkey in 2016 was investigated. For this purpose, a preliminary visual numerical analysis was conducted to form a three-dimensional topographic map, and the damage levels to which the buildings were subjected were estimated. Accordingly, in the aftermath of the explosion, a crater pit formed was formed, in addition to collapsed walls of buildings in the region. The explosion pressure also resulted in broken doors, windows along with their frames, broken glasses, and collapsed roofs. According to the results of the study, the amount of TNT, which was the main explosive in the attack, was calculated based on the level of damage caused by the explosion in the failures analysis. Finally, the amount of TNT that was calculated, and the levels of actual damages in the buildings, which were calculated by choosing a specific area in the region of the attack, were compared. The fact that the region where the attack occurred has a sloping topography and is full of trees at 1000 m altitude is a unique and authentic feature of this study in terms of theoretical and numerical analyses on the subject. Accordingly, it was determined that negative pressure could cause greater damage than positive pressure in large-scale explosions.
Keywords: Surface explosion; Reflection pressure; Failure analysis; Negative pressure; Positive pressure; Crater; Vehicle suicide attack